(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare effects of intravenous iron and blood transfusion on hemoglobin and retic count in pediatric patients with iron deficiency anemia (IDA) Methodology: This Comparative Cross-Sectional Study was conducted at Department of Pediatric, KRL Hospital, Islamabad, Pakistan, during August 2024 to December 2024. A total of 341 pediatric patients of either gender, aged 5-11 years, diagnosed with iron deficiency anemia with Hb <9 g/dL and failed to improve hemoglobin after 3 months of oral iron therapy with poor tolerance and good compliance and being admitted for parenteral iron therapy were included. Children with Hb 7-9 mg/dL were given IV iron sucrose whereas those with severe iron deficiency anemia Hb<7 g/dL and features of cardiovascular impairment were given packed RBC transfusion. Absolute reticulocyte count, hemoglobin and MCV were checked pre and post-treatment in both groups and difference of increase after treatment were noted and compared in both groups. Results: Out of 341, 252 (73.9%) patients had Hb (7-9 g/dL) who were given IV iron and 89 (26.1%) had Hb < 7 mg/dL meeting the criteria for transfusion. There was no significant difference in the ARC at 72-hours post intervention between the two groups (p=0.249). However, at 14 days post intervention the ARC increased significantly in IV iron therapy as compared to transfusion group (p<0.0001). The change in Hemoglobin (ΔHb) at 14 days had a median value 0.8 (0.3) g/dL in IV iron therapy as compared to 1.6 (0.3) g/dL in the transfusion group (p<0.0001). Conclusion: RBC transfusion acutely and transiently increased hemoglobin and retic count in IDA. However, IV iron therapy, while slower in improving Hb, offers a more sustained effect on red cell production.